До історії Таврики II—I ст. до н. е. - Зубар, В.М. (Археологія, 2003)
У статті на основі комплексу наявних джерел розглянуто питання історії пізніх скіфів і сарматів до і після походів Діофанта, сина Асклепіодора, — полководця понтійського царя Мітрідата VI Євпатора. В статье, открывающей серию работ, посвященных взаимоотношениям поздних скифов и сарматов, на основе комплекса источников рассмотрены вопросы истории этих народов во II-I вв. до н. э. Автором сделан вывод о том, что сарматы со II в. до н. э. периодически совершали набеги в Таврику, а в период херсонесско-скифских войн конца II в. до н. э. принимали в них участие на стороне скифов, хотя на основании имеющихся данных сейчас нельзя говорить о том, что в то время началась их миграция на территорию Поздней Скифии из-за Перекопа. После побед Диофанта над скифами их военный потенциал был значительно подорван, а сарматы, несмотря на поражение отряда Тасия, вероятно, вступили в союзные отношения с царем Понта Митридатом VI Евпатором. Все эти события не могли не отразиться на дальнейшей истории поздних скифов и основного центра античной цивилизации в Юго-Западной Таврике — Херсонеса. The present article is the first paper from the series of articles, researched into the interrelations of the late Scythians and Sarmatians. Based on the complex of sources it considers the number of questions on the history of these people in the 2nd - 1st centuries BC. The author draws up a conclusion that starting from the 2nd century BC Sarmatians were carrying out raids to the Taurica and during the period of the Chersonesos - Scythian wars at the end of the 2nd century BC they were participating in them on the Scythian part, though on the basis of the present data, one can’t state that starting with that time their migration to the Late Scythia territory from Perekop had begun. After Diophantos’ victories over the Scythians their military potential was considerably broken and the Sarmatians could have established the allied relations with the chieftain of Pontus Mithridates VI Eupatoros despite the loss of Tasius’ detachment. All of these events could have some reflection in the following history of the late Scythians and in the history of the mane center of the ancient Greek civilization in the South-Western Taurica - Chersonesos is.